Made to Measure: Options for Emissions Accounting under the UNFCCC - Prag, Andrew (OECD/IEA Climate Change Expert Group Papers, 2013)
Mitigation pledges put forward by countries under the UNFCCC process are "made to measure" in that they are tailored to fit each country's individual circumstances. However, the pledges also need to be made to be measured so that we have a full understanding of how the various commitments add up to an aggregate global mitigation effort. The Kyoto Protocol provides the only existing international emissions accounting framework, but it applies only to developed countries with specific commitments. This paper assesses what would be required, in addition to existing reporting requirements, to build a robust emissions accounting framework under the UNFCCC applicable to a broad range of Parties. The paper first identifies necessary building blocks for an emissions accounting framework and assesses progress made in agreeing international reporting processes. It then looks in detail at the two most challenging areas for emissions accounting. The first area is accounting for flows of tradable units from market-based mechanisms, including international flows between linked domestic trading systems as well as from offset crediting mechanisms. The second area is accounting for emissions and removals from the forestry and land-use sectors, which have characteristics that make emissions accounting challenging: the need to distinguish anthropogenic emissions from natural variations, to deal with long time-frames and to measure sinks as well as sources of emissions. Finally, options are presented for how these issues might be taken forward in the negotiations, and how negotiators can build on recent progress made on reporting formats